Conteúdo de DNA, número cromossômico e alguns compostos de interesse nutricional em Amaranthus spp - Samartini, Carolina Queiroz (2015)
The Amaranthaceae family consists of 170 genera and, within the family there the Amaranthus genus that is made up of 60 species. In Brazil the species is widely known as pigweed and there are the least 10 of this species. Despite researches show the benefits of these specie for human consumption, their consumption is very little and is seen as plant weed. The objective of this study was to determine the chromosome number, nuclear DNA content, as well as post-harvest characterization of Amaranthus species. In this research were used five species of the genus collected from the germplasm collection of unconventional vegetables at the Universidade Federal de Lavras (UFLA), MG, Brazil. The metaphase chromosomes were obtained by technique of drying on flame and dyed with 2 % Giemsa. The nuclear DNA content was estimated by the flow cytometry using LB01 and Pisum sativum buffer as standard. In order to accomplish the objectives were carried out the following postharvest analyses: antioxidant activity (DPPH and ABTS), phenolic compounds, vitamin C, total soluble solids, pH, moisture, colour (L *, a *, b *, Chroma, °Hue), lipids and proteins. The number of chromosome varied from 2n = 32 (A. hybridus) and 2n = 34 (A. spinosus, A. viridis, deflexus and A. retroflexus), therefore is disploidy. The nuclear DNA content to the species ranged from 1.28 pg to 1.79 pg. The highest value observed for A. deflexus (1.79 pg). Although it has been observed that the DNA content in A. deflexus, this species also had 2n = 34 chromosomes, and there are no relationship between number of chromosomes and nuclear DNA content. Regarding post-harvest characterization, data analysis revealed that the five species of Amaranthus have nutritional potential for human consumption, with phenolic content of 10.98 mg 100 g -1 and 763.52 mg 100 g -1 , Vitamin C 109.20 mg 100 g -1 to 174.18 mg 100 g -1 , antioxidant activity by DPPH method between 41.76 % to 88.22 % SRL SRL and the ABTS method of 10.53 µM trolox g -1 to 16.48 g -1 µM Trolox, over commonly consumed vegetables.